The risk of infections in patients with myelodysplastic syndromes in 2016. Issue 6 (2nd June 2016) - Caira, Morena; Latagliata, Roberto; Girmenia, Corrado
ABSTRACT: Introduction : The medical treatment of patients suffering from myelodysplastic syndromes has significantly changed during the last ten years, and this may have impacted the epidemiology of infectious complications. Some 'real world' experiences raised the issue of infections in this setting and the possible negative consequences for patients and health system: the higher the rate of hospitalizations and need for anti-infective therapies, the higher the treatment delays/withdrawal and consecutive the worse the outcome. Areas covered : The main epidemiological data on myelodysplastic patients are reviewed. Potential risk factors are described, including those related to the disease itself, patient's characteristics, health conditions and the environment. Expert commentary : The complexity of MDS treatment is expected to increase further, with the introduction of other drugs and combined therapies. Defining the level of risk at time of treatment prescription will become more and more important, in order to better manage the infectious risk and the febrile events eventually occurring.